Von der schematischen Charakteristik bis zur ausgefeilten Ethnographie: der Blick auf die Fremden durch die Alten Ägypter - Quack, Joachim Friedrich (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2016)
This paper traces through time how the Ancient Egyptians conceptualized their neighbors, sometimes with rather global models of few entities, sometimes with genuine interest in ethnographic details. It is analyzed how such texts are linked with their respective political situations. Obviously, periods of intensified contact go hand in hand with more detailed information about foreign customs. In one case concerning a detailed ethnographic treatise, similarities with Greek compositions (e. g. Herodotus) are to be noted, and dependency of a non-preserved Greek text has to be considered as a serious possibility.